Aspek Materi, Konstruksi dan Bahasa pada Soal Sastra Ujian Nasional Tingkat SMK Mata Pelajaran Bahasa Indonesia Tahun 2014/2015 - Ariningrum, Wening, Dra. Main Sufanti, M.Hum (2016)
This study aimed to describe the feasibility of: (1) a material aspect in the literature about the National Examination subjects Indonesian vocational level in 2014-2015, (2) construction aspects of the literature about the National Examination subjects Indonesian vocational level in 2014-2015, ( 3) aspects of language in literature about the National Examination subjects Indonesian vocational level in 2014-2015.The method used in this research is descriptive qualitative. The data used in this study is about literature National Exam tipe I. Sources of data in this study is about the Indonesian National Exam Level Vocational years 2014-2015 with 20 type of questions. The data collection technique used is the study documentation Validation data using triangulation theory. Data were analyzed using content analysis. The results of this study were (1) based on the characteristics of the material aspects, eight matter of this literature is declared eligible by 100%; (2) on the construction aspects declared eligible by 62.5%, while the less worthy of 37.5%; (3) the language aspect about this literary declared eligible by 75%, while the less worthy of 25%.In the aspect of construction that is not in accordance with these characteristics, there are three questions that are not in accordance with the length of options jawabaan relatively similar; eight about not using images, tables, graphs and the like; as well as all the answer choices is not their choice of answers-shaped figure / time arranged in order / chronology. While on aspects of language are less suitable for the two problems are not according to the rules on the use of spelling Indonesian, and two options to repeat the word / group of the same word. Keyword : about literature, material aspects, aspects of construction, aspects of language